A second species of Araucariocladus Silveira & Mermudes, with notes on the variation in antennomere numbers in this genus (Coleoptera: Lampyridae) - Nunes, V.c.s.; Souto, P.m.; Monteiro, R.f.; Silveira, L.f.l. (Zootaxa, 2019)
Here, we describe Araucariocladus amfractus sp. nov., and compare it to the previously monotypic type-species, A. hiems. The new species can be distinguished from A. hiems by the following combination: colour pattern overall dark-brown; pedicel three times shorter than antennomere III and slightly wider than long; distance between antennal sockets as wide as 3/5 clypeal width; labial palpomere III with sides divergent towards apex, apical margin longer than dorsal and shorter than ventral margin; pronotum 1.5x wider than long, anterior margin somewhat sinuose, with a shallow angle anteriad, posterior margin almost straight. A. amfractus sp. nov. is, prima facie, endemic to the Itatiaia Massif, part of the Mantiqueira Mountain Range, Southeastern Brazil. We provide illustrations of the diagnostic features, and an occurrence map for the Araucariocladus species. Finally, we report a previously unrecognized intra-specific variation in the antennomere numbers of A. hiems, a feature also present in Araucariocladus amfractus sp. nov., and adjust the generic diagnosis to include species with 17 or 18 antennomeres. [Zoobank LSID: urn:lsid:zoobank.org:act:C335B064-FBD4-4256-983D-B17DF06BAA0D]